2021
DOI: 10.1155/2021/8868720
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Auricular Acupressure in Prevention and Treatment of Chemotherapy-Induced Nausea and Vomiting in Patients with Cancer: A Systematic Review and Meta-Analysis

Abstract: Background. More than 40% of patients with cancer have reported that chemotherapy-induced nausea and vomiting (CINV) remained the most debilitating side effects of treatment even in the era of new antiemetics. Objective. The purpose of this review was to systematically evaluate the clinical effect of auricular acupressure (AA) in prevention and treatment of chemotherapy-induced nausea and vomiting. Methods. The following databases were searched: PubMed, Cochrane Library, EMBASE, the Web of Science, Chinese Bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
0
11
0
4
Order By: Relevance
“…The study designs of the 2 guidelines were complete and of high quality; all were approved for inclusion. Among the 13 included systematic reviews [ 17 , 29 ], 6 were in English literature [ 17 , 19 , 21 , 22 , 24 , 27 ], and 7 were in Chinese [ 18 , 20 , 23 , 25 , 26 , 28 , 29 ]. The methodological quality of the 13 systematic reviews is shown in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The study designs of the 2 guidelines were complete and of high quality; all were approved for inclusion. Among the 13 included systematic reviews [ 17 , 29 ], 6 were in English literature [ 17 , 19 , 21 , 22 , 24 , 27 ], and 7 were in Chinese [ 18 , 20 , 23 , 25 , 26 , 28 , 29 ]. The methodological quality of the 13 systematic reviews is shown in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…(1) Auricular Point Therapy . Auricular point therapy can be used as an adjuvant therapy in the prevention and treatment of CINV [ 17 ]. This therapy regulates a patient's physical and psychological function through meridians and acupoints; it is noninvasive, has relatively few side effects, safe, effective, and affordable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Auricular acupressure (AA) is a noninvasive treatment in traditional Chinese medicine technique, and it has been proved to be a valuable strategy to improve menstrual symptoms through pressing vaccaria, magnetic beads and cowherb seeds sticked on auricular acupoints corresponding to all parts of the human body ( 6 , 7 ). As a typical traditional Chinese medical therapy using acupoints without needle insertion, AA stimulates acupoints by pressure from fingers or automatically by the seeds themselves ( 8 ).…”
Section: Introductionmentioning
confidence: 99%